2020
DOI: 10.21831/jipi.v6i1.28109
|View full text |Cite
|
Sign up to set email alerts
|

Blended-flipped classroom learning for physics students with the topic of the photoelectric effect

Abstract: Blended-Flipped Classroom Learning is a learning method that combines blended learning with flipped classroom learning. This study aims to: (1). Design and implement Blended-Flipped Classroom Learning with the topic of Photoelectric Effect for Physics and Physics Education students in Modern Physics course; (2). Determine how the effect of Blended-Flipped Classroom Learning on student learning outcomes for the topic of Photoelectric Effect; (3). Determine students’ responses toward Blended-Flipped Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Research results show that blended learning produces a stronger sense of community between students than traditional learning or online learning. Students' perceptions of online classes show an excellent category because the teacher can facilitate a good, dynamic and objective effective learning climate in evaluation (Boelens et al, 2017;Pattiserlihun & Setiadi, 2020) Technically, there are various models in the development of blended learning that can be applied both online and offline; online and offline model of face-to-face learning, using an electronic module, combining learning with texts, audio, and multimedia (web-based). As part of blended learning, web-based instructional materials can provide teachers and students with a broad range of new and exciting experiences that sometimes are impossible to duplicate in a traditional classroom.…”
Section: -18mentioning
confidence: 99%
“…Research results show that blended learning produces a stronger sense of community between students than traditional learning or online learning. Students' perceptions of online classes show an excellent category because the teacher can facilitate a good, dynamic and objective effective learning climate in evaluation (Boelens et al, 2017;Pattiserlihun & Setiadi, 2020) Technically, there are various models in the development of blended learning that can be applied both online and offline; online and offline model of face-to-face learning, using an electronic module, combining learning with texts, audio, and multimedia (web-based). As part of blended learning, web-based instructional materials can provide teachers and students with a broad range of new and exciting experiences that sometimes are impossible to duplicate in a traditional classroom.…”
Section: -18mentioning
confidence: 99%
“…In recent years, there has been a growing interest in exploring the effectiveness of flipped classrooms on student learning outcomes in various educational contexts. Several studies have investigated the impact of the flipped classroom model on student learning outcomes in the field of chemistry education (Pattiserlihun & Setiadi, 2020). One notable study conducted by Baepler, Walker, & Driessen (2014) found that the use of flipped instruction in a college chemistry course resulted in learning outcomes that were either statistically equal to or superior to traditional classrooms (Martin et al, 2016).…”
Section: ▪ Introductionmentioning
confidence: 99%
“…Based on previous research, the blended-flipped classroom model can help students to obtain more optimal learning outcomes (Pattiserlihun et al, 2020;Hasanah et al, 2021), improve students' creative thinking skills and creative innovation (Rahajeng et al, 2018;Wannapiroon & Petsangsari, 2020), increase students' self-efficacy and conceptual mastery (Yanah et al, 2018), increase students' learning achievement and independence (Choiroh et al, 2018), and increase students' critical thinking skills (Zulhamdi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%